2007
DOI: 10.1002/chem.200700076
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interactions and Internal Dynamics in Dimethoxymethane–Water

Abstract: The millimeter-wave absorption and Fourier transform microwave spectra of five isotopologues of the 1:1 adduct of dimethoxymethane-water have been measured in supersonic expansions. Each rotational transition appears as a quintuplet, due to the internal rotation of the two methyl groups, which are nonequivalent in the adduct. The water moiety, linked asymmetrically to dimethoxymethane, behaves as a proton donor to one of its oxygen atoms and interferes with the internal rotation of the farther methyl group thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Ab initio calculations were performed using the secondorder Møller-Plesset (MP2) perturbation theory [19] with the 6-311 + + GA C H T U N G T R E N N U N G (d,p) basis set. [20] The MP2/6-311 + + GA C H T U N G T R E N N U N G (d,p) level of theory was chosen because it provided astonishingly good agreement between the predicted and the experimentally observed geometries for several van der Waals [21] and hydrogen-bonded complexes [22] in a number of previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ab initio calculations were performed using the secondorder Møller-Plesset (MP2) perturbation theory [19] with the 6-311 + + GA C H T U N G T R E N N U N G (d,p) basis set. [20] The MP2/6-311 + + GA C H T U N G T R E N N U N G (d,p) level of theory was chosen because it provided astonishingly good agreement between the predicted and the experimentally observed geometries for several van der Waals [21] and hydrogen-bonded complexes [22] in a number of previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…The superior performance of 6-311 + + G-A C H T U N G T R E N N U N G (d,p) in geometry predictions had been reported before. [17,18,21,22] Another quantity obtained from the experiments and the calculations is the electric dipole moment component. It was reported that the MP2 density predicts the electric dipole moment components more accurately than the HF density.…”
Section: Discussionmentioning
confidence: 99%
“…However, considerable perturbations are induced by water also in its proton donor role. For example, it changes the barriers to internal rotation of the methyl group with respect to the isolated molecule in the cases of dimethoxymethane-water, 32 diacetyl-water, 30 and of trans-N-methylformamide-water. 33 The two equivalent methyl groups have different barriers in dimethoxymethane-water and diacetylwater, since that water interacts more specifically with one of them.…”
Section: Water Perturbing the Dynamics Of Internal Motions Of The Par...mentioning
confidence: 99%
“…[12] Acetone (CH 3 COCH 3 ), the simplest ketone,i sasmall molecule with C 2v symmetrya nd two CH 3 tops generatingw ide internalr otation splittings. [17] In the van der Waals complex of acetone-argon, the two methyl groups undergo hindered internal rotationr esulting in as plitting of each rotational transition into four or five components. [13] Earlier rotational studies have indicated that complexation can affect the internal rotationb arriero famolecule bearing am ethylg roup.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of p ‐fluorotoluene–argon, the molecular symmetry changes upon complexation, which introduces a three‐fold internal rotation potential with respect to the pure six‐fold potential in the monomer. For dimethoxymethane, there are two different values for the potential barriers to the rotation of the two equivalent internal rotors upon formation of a complex with a water molecule . In the van der Waals complex of acetone–argon, the two methyl groups undergo hindered internal rotation resulting in a splitting of each rotational transition into four or five components.…”
Section: Introductionmentioning
confidence: 99%